Efektivitas Pendekatan Pestel dalam Merancang Kebijakan Pendidikan Berbasis Teknologi - Khairul Tri Anjani; Anna Rufaidah; Henny Suharyati (STKIP Pesisir Selatan, 2024)
Research by UNESCO shows that around 50% of the world's population does not have access to the internet, which is a major barrier to the application of technology in education. In today's digital age, there are great advances in technology that enable educational innovation and improved learning quality. However, technology implementation requires comprehensive and inclusive policies that consider technological, environmental, political, economic and social aspects. The purpose of this study is to study, understand and explain the importance of technology in education; and to make an analysis of strategies that use technology to make educational policies. This study uses a qualitative method with a PESTEL analysis approach and descriptive analytics to elaborate on this. The secondary data used in this study came from government reports, publications of educational institutions, scientific articles and other relevant official documents. The results show that PESTEL analysis is a useful technique for making technology-based education plans. Technology infrastructure, various trainings, and the effectiveness of technology adoption in education require adequate political and budgetary support, as well as positive community and academic support.